To determine if these pairs of expressions are equivalent, we can simplify both expressions and see if they yield the same result.
Let's simplify the first expression:
3 + 14(x-5) + 1
= 3 + 14x - 70 + 1 (distributing the 14)
= 14x - 66
Now let's simplify the second expression:
14(x-5) + 4
= 14x - 70 + 4 (distributing the 14)
= 14x - 66
As we can see, both expressions simplify to 14x - 66. Therefore, the pair of expressions are indeed equivalent.
tell whether these pairs of expressions are equivalent.
3+14(x-5)+1 and 14(x-5)+4
1 answer